Length–length relationships for the main shark species caught in the commercial shark fisheries of Western Australia. (14th February 2023) - Bartes, Saia Nahir; Braccini, Matías
Abstract: Length–length relationships are presented for 19 shark species caught in the commercial shark fisheries of Western Australia. A robust linear regression model was used to estimate the relationship between interdorsal, total and fork lengths. Sharks are typically landed as trunks, so information generated in our study is essential for converting partial lengths to total lengths for reconstructing catch composition, an essential step for assessing the status of shark populations. Resumen: En este estudio se presentan las relaciones de longitud‐longitud para 19 especies de tiburones capturadas en las pesquerías comerciales de Australia Occidental. Se utilizó un modelo de regresión lineal robusto para estimar la relación entre las longitudes interdorsal, total y de horquilla. Dado que los tiburones se desembarcan generalmente incompletos, la información generada en este estudio es esencial para convertir las tallas parciales en tallas totales y por lo tanto, reconstruir las composiciones de las capturas, lo que es considerado esencial para evaluar el estado de las poblaciones de tiburones.